Synthesis and properties of cotton fabric functionalized by dimethyl phosphite and perfluorohexyl group grafted graphene oxide. Issue 6 (30th August 2019) - Xu, Jia; Zhang, Jingyu; Xu, Jiahan; Miao, Guangyuan; Feng, Long; Zhang, Zhanzhu; Zhang, Huanxia
Abstract : Purpose: Nanotechnology has been able to bind to a wide range of functional textiles in recently. This paper aims to modify graphene oxide (GO) by grafting dimethyl phosphite and perfluorohexyl iodine. It was applied to cotton to obtain a flame-retardant, water-repellent and ultraviolet-resistant multifunctional fabric. Design/methodology/approach: The GO-multi was synthesized by grafted dimethyl phosphite and perfluorohexyl chain and applied to cotton by the dipping-drying method. The surface chemistry of functionalized GO was characterized by Fourier transform infrared spectroscopy and X-ray photoelectron spectroscopy. The thermal stability of the fabric was characterized by thermogravimetric analysis (TGA). The combustion properties were evaluated using a microscale combustion calorimeter, match test and TGA. Hydrophobicity of film and fabric surface was characterized by static contact angle, and the UV resistance of the fabric was represented by the ultroviolet procetion factor (UPF) value. Findings: Dimethyl phosphite and perfluorohexyl chains were grafted on the surface of GO successively. In the match test, the GO-multi/cotton kept the original outline of the fabric. According to the micro-scale combustion calorimetry (MCC) data, the value of PHRR and THR of GO-multi/cotton was about 45 per cent lower than that of untreated cotton fabric. It was found from the field-emission scanning electron microscopy (SEM) pictures that the residue of GO-multi/ cotton burned by the match method was more compact and the graphene lamellar structure remained more complete. The hydrophobic effect of GO-multi/cotton was improved compared to untreated cotton, but not better than the fabric treated by the perfluorohexyl chain-grafted GO. The UPF value of GO-multi/cotton reached 253, which indicated that the anti-ultraviolet performance of GO-multi was greatly improved after it was deposited on the cotton fabric. Research limitations/implications: Although the hydrophobic effect was much higher than that of untreated cotton fabric, its hydrophobic effect was not satisfied, which may be due to the fact that the content of F element content was low. So, it is still needed to explore the modifying method to increase the functional component amount on the GO nanosheet. Practical implications: This modifying method can be used in any of multifunctional textile preparation process. The hydrophobic and flame-retardant cotton fabric revealed a sample for use in outdoor sports such as clothes and tents. Originality/value: To meet the needs of multifunctional cotton fabrics, the modification of GO with dimethyl phosphite and perfluorohexyl iodine has not been reported. The modified fabric has flame-retardant, UV-resistant and hydrophobic properties.